2015
DOI: 10.1016/j.jbankfin.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Stock market dispersion, the business cycle and expected factor returns

Abstract: We provide evidence using data from the G7 countries suggesting that return dispersion may serve as an economic state variable in that it reliably predicts time-variation in economic activity, market returns, the value and momentum premia and market volatility.A relatively high return dispersion predicts a deterioration in business conditions, a higher value premium, a smaller momentum premium and lower market returns.Dispersion based market and factor timing strategies outperform out-of-sample buy and hold st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 55 publications
8
34
0
Order By: Relevance
“…Despite its modest magnitude at peak (0.02%), the impact of stock market dispersion on the unemployment rate is relatively long-lived, with the responses lasting beyond the 20-month horizon. Our result is consistent with previous studies that use U.S. data (e.g., Loungani, Rush, andTave 1990, andmore recently Angelidis, Sakkas, andTessaromatis 2015) in the sense that unemployment significantly depends on the lags of stock market dispersion.…”
Section: Stock Market Dispersion and The Unemployment Ratesupporting
confidence: 93%
See 1 more Smart Citation
“…Despite its modest magnitude at peak (0.02%), the impact of stock market dispersion on the unemployment rate is relatively long-lived, with the responses lasting beyond the 20-month horizon. Our result is consistent with previous studies that use U.S. data (e.g., Loungani, Rush, andTave 1990, andmore recently Angelidis, Sakkas, andTessaromatis 2015) in the sense that unemployment significantly depends on the lags of stock market dispersion.…”
Section: Stock Market Dispersion and The Unemployment Ratesupporting
confidence: 93%
“…Fortin and Araar () study the effects of stock market dispersion using Canadian data. Recently, Angelidis, Sakkas, and Tessaromatis () find that returns dispersion can help predict variation in economic activity using a Probit regression with data from G‐7 countries. While also exploring the panel nature of the data, their approach is different from our panel VAR approach that highlights both the cross‐sectional heterogeneity and the dynamic nature of cross‐country interdependencies.…”
mentioning
confidence: 99%
“…The results are consistent with findings in Hwang and Satchell (2005) and Byun (2016) that adding information in the cross-sectional dispersion helps better specify the daily volatility process. They are also in line with the evidence in Angelidis et al (2015), Connolly and Stivers (2006), and Stivers (2003), which document a positive relation between dispersion measures and future market-level volatility. The implication is that a higher dispersion measure is linked to a higher market volatility, indicating a deterioration of financial conditions.…”
Section: Introductionsupporting
confidence: 87%
“…Low cross-sectional dispersion implies that investors, both retail and institutional, follow each other in and out of the same stocks due to information cascade or behavioral biases especially during extreme market conditions (Chang et al, 2000;Choi and Sias, 2009;Christie and Huang, 1995;Lakonishok et al, 1992;Li et al, 2017;Yao et al, 2014). This underscores another inherent link between return dispersion and market volatility (Angelidis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…5 Liu et al [42] showed that a rectification by the factor 1/s 1/2 is necessary. 6 In wavelet applications, it is common to raise the squared local amplitude to a further power in order to accentuate contrast in the corresponding heat map; see, e.g. Percival and Walden [47].…”
Section: Morlet Waveletsmentioning
confidence: 99%